Tyrosine-kinase inhibitors for lung or breast cancer and drug–drug interactions: a clinical guide - Santamaria, Fiorenza; Roberto, Michela; Maltese, Giulia; Nicolella, Francesco; Torchia, Andrea; Buccilli, Dorelsa; Di Civita, Mattia Alberto; Giancontieri, Paola; Marinelli, Daniele; Cirillo, Alessio; Bianco, Vincenzo; Verrico, Monica; et al. (Oncology Reviews, 2025)
IntroductionIn the last two decades, tyrosine-kinase inhibitors (TKIs) have dramatically changed the prognosis of lung and breast cancers, with significant benefits in the metastatic setting and, more recently, in the adjuvant setting for selected groups of patients. Despite their favorable oncological effects, TKIs carry a high risk for drug–drug interactions (DDIs) due to their pharmacokinetics (PK), which depend on both pH-dependent absorption and liver metabolism. However, DDIs are frequently related to “potential DDIs” (pDDIs), and their clinical relevance is often underestimated; there is also a lack of practical guidance for clinicians.Methods and materialsWe conducted a narrative review restricted to the last 20 years, involving adult individuals (aged 18 years or older) with lung or breast cancers treated with TKIs and clinical data on potential DDIs, along with reported toxicities or outcomes.ResultsWe summarized the pharmacokinetic profiles and the clinical evidence of 11 TKIs used for lung or breast cancers. Moreover, we provided an easy-to-use guide to help physicians in clinical practice with recommended dose adjustments or cautions necessary to prevent severe adverse events or possible changes in TKI availability in the presence of other interfering drugs.ConclusionThe level of evidence for DDIs during TKI treatment is low because most available data are from phase I studies in healthy volunteers and few phase II studies in cancer patients. However, since the occurrence of DDIs can be clinically significant and a prompt drug reconciliation process can be useful to prevent them, further prospective, large-sample-size clinical trials should be carried out.